PROBLEMAS AMBIENTALES Y SUS EFECTOS EN EL DESARROLLO TURÍSTICO DE LA PROVINCIA DE LOS RÍOS 2023. - Zavala Arrunategui, Paola Katherine (2023)
Environmental problems had adverse effects on the tourism development of the province of Los Ríos in 2023, decreasing its attractiveness for visitors and compromising the long-term sustainability of the local tourism industry. To address these challenges, concerted action would be required at the government, community and business levels to implement environmental conservation measures and promote sustainable tourism practices. The objective of this study was to analyze environmental problems and their effects on tourism development in the province of Los Ríos. The research development methodology was carried out by applying a survey to a sample of the inhabitants of the province of Los Ríos to know the opinion of the population regarding the problem. Among the results, it was obtained that the inhabitants do not know the environmental problems of the province, however, they infer that the rivers could have the greatest impact and this prevents there from being an adequate development of the tourism sector. Therefore, despite the slow growth of the sector in terms of environmental care, it is necessary to formulate strategies that mitigate these impacts, considering team and inter-institutional work to achieve greater effectiveness in the application of the solutions proposed on the intervention of principles sustainable based on strategic planning aimed at strengthening tourism activity and environmental care.